In vitro callus induction of gerbera from leaf explant - Afrin Jui, Sadia; Mijanur Rahman Rajib, Md.; Mofazzal Hossain, M.; Rani Mallik, Sharmila; Jahan Nur, Iffat; Ferdush, Jannatul (International Journal of Advanced Geosciences, 2020)
The experiment was designed to evaluate the effect of growth regulators on leaf explant of Gerbera for callus induction. Various kinds of plant growth regulators such as 6-Benzylaminopurine (BAP), Î±-Naphthalene acetic acid (NAA), 2, 4-Dichlorophenoxyacetic acid (2, 4-D), Indole-3-acetic acid (IAA) were used to initiate cultures. These were added to Murashige and Skoog medium in different combinations and concentrations. Leaf explants cultured on MS medium supplemented with BAP+ 2, 4-D+ IAA in T4 treatment & BAP+ 2,4-D in T5 treatment showed the best results for callus induction. On the other hand callus was induced early in the combination of BA+ 2,4-D + IAA hormone in T5, T9 & T8 treatment respectively. The rate of callus induction was very low in BA + NAA combinations but it was much earlier.Â Â Â